ANALISIS DAN PENGEMBANGAN SITUS RESMI PARIWISATA INDONESIA DAN SISTEM INFORMASI PENDUKUNGNYA - Handijaya Dewantara, Made (Jurnal Master Pariwisata (JUMPA); Volume 01, Nomor 02, Januari 2015, 2015)
There is a gap between the growth of internet utilization for tourism industry in Indonesia and unfortunate situation where showed from the rank of Indonesia in tourism and travel competitiveness index. In order to solve this problem, this research was conducted with three objectives as follows: to know the characteristics (strength and weakness) of current Indonesia tourism official website by a comparison with other official tourism website; to analyze the visitor’s opinions about the current Indonesian tourism official website; and to develop the new content of Indonesia tourism official website including its information system. By using a qualitative descriptive analysis, it is found that the Indonesia official tourism website still has several weaknesses particularly on its content including languages variances, visa information, currency conversion, and direction or transportation, and also has several strengths particularly to display the diversity about Indonesia, through excellent photo gallery.